Longitudinal Trajectories of Fasting Plasma Glucose and Risks of Cardiovascular Diseases in Middle Age to Elderly People Within the General Japanese Population: The Suita Study. Issue 3 (5th February 2019) - Ogata, Soshiro; Watanabe, Makoto; Kokubo, Yoshihiro; Higashiyama, Aya; Nakao, Yoko M.; Takegami, Misa; Nishimura, Kunihiro; Nakai, Michikazu; Kiyoshige, Eri; Hosoda, Kiminori; Okamura, Tomonori; Miyamoto, Yoshihiro
Abstract : Background: Few previous studies used information on changes in fasting plasma glucose (FPG) assessed at multiple points in time in relationship to cardiovascular disease (CVD) incidence. The present study aimed to identify subgroups of FPG trajectories with assessing CVD incidence. Methods and Results: The present study was based on the Suita study, a population‐based cohort study in Japan. The primary outcome was incidence of the first CVD events consisting of stroke and coronary heart diseases between 1989 and 2013. The main exposure was FPG assessed every 2 years. We used joint latent class mixed models to derive FPG trajectories over time while evaluating cumulative incidence of CVD, and categorized participants into several subgroups based on those trajectories and cumulative incidence. We observed 356 and 243 CVD events during the median follow‐up of 17.2 and 20.2 years among 3120 men and 3482 women, respectively. The joint latent mixed models found 3 subgroups in men and 2 subgroups in women. Of the 3 subgroups in men, 1 subgroup had FPG levels that increased sharply (96.5–205.0 mg/dL from aged 40 to 80 years) and higher CVD cumulative incidence. Of the 2 subgroups in women, 1 subgroup had FPG levels that increased sharply (97.7–190.5 mg/dL from aged 40 to 80 years) and tended to have slightly higher CVD incidence compared with the other subgroup. Conclusion: It can be important to manage CVD risk factors especially for people whose FPG trajectories sharply increased to prevent CVD.